Electrochemical corrosion resistance of thermal oxide formed on anodized stainless steel. Issue 2 (9th April 2021) - Deng, Hongda; Liu, Yongliang; He, Zhen; Gou, Xiantao; Sheng, Yefan; Chen, Long; Ren, Jianbing
Abstract : Purpose: The purpose of this paper is to investigate and explain thermal oxide effect on electrochemical corrosion resistance anodized stainless steel (SS). Design/methodology/approach: Electrochemical corrosion resistance of thermal oxides produced on anodized 304 SS in air at 350°C, 550°C, 750°C and 950°C in 3.5 wt.% NaCl solution have been investigated by dynamic potential polarization, EIS and double-loop dynamic polarization. Anodized 304 SS were obtained by anodization at the constant density of 1.4 mA.cm -2 in the solution containing 28.0 g.L -1 H3 PO4, 20.0 g.L-1C6 H8 O7, 200.0 g.L -1 H2 O2 at 70°C for 50 min. SEM and EDS had been also used to characterize the thermal oxides and passive oxide. Findings: Interestingly, anodized 304SS with thermal oxide produced at 350°C displayed more electrochemical corrosion and pitting resistance than anodized 304 SS only with passive oxide, as related to the formation of oxide film with higher chromium to iron ratio. Whereas, anodized 304SS with thermal oxide formed at 950°C shows the worse electrochemical corrosion and pitting resistance among those formed at the high temperatures due to thermal oxide with least compact. Originality/value: When thermally oxidized in the range of 350°C–950°C, electrochemical corrosion and pitting corrosion resistance of anodized 304 SS decrease with the increase of temperature due to less compactness, more defects of thermal oxide.